PENGARUH KOORDINASI TERHADAP IMPLEMENTASI PROGRAM KELUARGA BERENCANA DI KECAMATAN SIMPANG HILIR KABUPATEN KAYONG UTARA - Fitri Dwi Haryani E.42008071 (FISIP Universitas Tanjungpura Pontianak, 2012)
Title of this study is “influence the coordination of the implementation of family planning in the subdistrict Simpang Hilir Kayong Utara districts”. This research aims to identify and analyze the influence the coordination of the implementation of family planning in the subdistrict Simpang Hilir Kayong Utara districts. This researchis included in the explanatory research with quantitative analysis and using the theory by Djamin of coordination and theory by Van Meter and Van horn of the implementation of public policy. The results of the field study showed that coordination is carried out by the implementing agency for family planning programs give a good contribution of 0,316 the implementation of the family planning program so that coordination should be improve to help implementation of family planning programs more effectively. In addition, coordination has a regression coefficient of 0,972 the implementation of the family planning program.KeyWords : coordination, implementation of the program and the influence